On the road to stable, isolable [4]cumulenes: Reactivity and cyclization reactions - Johnson, Matthew A.; Meckes, Jakob A.; Bühringer, Martina; Zhou, Zheng; Kuwatani, Yoshiyuki; Ferguson, Michael J.; Wei, Zheng; Iyoda, Masahiko; Petrukhina, Marina A.; Tykwinski, Rik R. (Journal of Physical Organic Chemistry, 2022)
The design and synthesis of persistent tetraaryl[4]cumulenes are reported. Derivatives with phenyl endgroups ([4]Ph and [4]Ph/Ar*) are susceptible to reactions during synthesis and/or purification that complicate isolation of the desired product, particularly intermolecular dimerization reactions. Incorporation of (3,5-di-tert-butyl)phenyl endgroups (Ar*) provides increased stability, culminating in the stable and isolable [4]cumulene [4]Ar*. Cumulene [4]Ar* remains, however, susceptible to dimerization under pressing conditions, and [4]Ar* also readily reacts with electrophiles under mild conditions that lead to intramolecular cyclization. Given the structural complexity of the side products in these studies (compounds 3, 10, 14, 17, 18), X-ray crystallography plays a vital role in their identification.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cycloadditions; radialenes; X-ray crystallography; [4]cumulenes; [n]cumulenes